FACTORS RELATED TO DEPRESSION AMONG OLDER PEOPLE LIVING IN CIMAHI, WEST JAVA PROVINCE, INDONESIA - Kiki Gustryanti; Sunanta Thongpat; Sonthaya Maneerat (Belitung Raya Foundation, Indonesia, 2017)
Background: Depression is commonly found in older people. The prevalence of depression among older people, particularly in Indonesia is increasing worldwide. Objective: This study aimed to identify the factors related to depression among older people living in Cimahi, West Java Province, Indonesia. Method: A cross sectional design was used with a total of 267 older people aged from 60 to 79 years old. A multi-stage random sampling was used in five public health centers in Cimahi. The instruments comprised of socio-demographic questionnaires, general health perceptions questionnaire, Chula Activities of Daily Living Index (CADLI), and Geriatric Depression Scale-15 (GDS-15). Data analysis was conducted using descriptive statistic, chi-square, and point-biserial. Results: The result revealed that 56.2% of respondents were no depression and 43.8% of respondents was depression. The results also showed that age, marital status, family history of depression, perceived health status, and activities of daily living was significant relationship with depression among older people (p<.01; p<.05). Conclusion: This finding can be used as a reference to implement new strategies to decrease depression among older people. This article has been corrected with a separate erratum: https://doi.org/10.33546/bnj.1141